Integrated institutional model and API-based information system for seaweed agribusiness governance in South Sulawesi, Indonesia - BUDIMAN HARUNA; YUNARTI YUNARTI; WAHYUNI ZAM (Smujo International, 2026)
Abstract. Haruna B, Yunarti, Zam W. 2026. Integrated institutional model and API-based information system for seaweed agribusiness governance in South Sulawesi, Indonesia. Asian J Agric 10 (1): g100170. https://doi.org/10.13057/asianjagric/g100170. This study aimed to strengthen the governance of the seaweed agribusiness value chain in South Sulawesi, Indonesia, by developing an integrated institutional model and API-based information system. Preliminary analysis shows that the value chain is still characterized by information asymmetry, the dominance of intermediaries in market access, weak coordination between actors, and the lack of digital recording and consistent quality standards. This condition increases the cost of information, negotiation, and monitoring, and limits the bargaining position of farmers. The research uses a qualitative case study approach through in-depth interviews, FGD, document analysis, and expert validation. The data is thematically analyzed to map the actors, governance relationships, and main sources of transaction costs. The results of the analysis were used to design a new institutional model that strengthens the role of cooperatives and farmer groups as nodes for coordination, data consolidation, and collective negotiation, while improving working relationships with local governments, financial institutions, exporters, and universities. The model is operationalized through an API-based information system that supports data exchange, production recording, market demand, and documentation of transactions between actors. Validation is carried out through simulation-based functional testing of key operational scenarios, including production recording, market demand delivery, harvest ordering, and data synchronization between authorized users. The test results showed that the system was able to run key process flows consistently and provide a more transparent digital footprint for coordination needs. In agribusiness, this design has the potential to increase marketing certainty, assist production planning based on demand, accelerate coordination between sectors, and reduce farmers' reliance on informal information. Theoretically, these findings suggest that digitalization for smallholders will be more effective if it is accompanied by institutional restructuring, not just technology adoption. The developed system has achieved functional feasibility as the basis for pilot implementation and advanced field evaluation in South Sulawesi.